Using Reading Guides and On-line Quizzes to Improve Reading Compliance and Quiz Scores - Trent Maurer; Judith Longfield (International Journal for the Scholarship of Teaching and Learning, 2015)
This study compared students’ daily in-class reading quiz scores in an introductory Child Development course across five conditions: control, reading guide only, reading guide and on-line practice quiz, reading guide and on-line graded quiz, and reading guide and both types of on-line quizzes. At the beginning of class, students completed a 5-item quiz over the assigned readings. With the exception of the control section, all students had access to an instructor-designed reading guide for each of the 20 assigned readings. Results revealed that reading guides significantly increased student learning as demonstrated by increased scores on the in-class reading quizzes, with marginal additional gains when practice quizzes were also utilized. The addition of on-line graded quizzes resulted in lower scores on in-class quizzes. Results held even after multiple subsidiary analyses controlling for time spent studying. These findings suggest that reading guides may be a valuable study aid for improving student learning.